LB0012 HEADLINE RESULTS FOR A PHASE 4, 52-WEEK, RANDOMISED, DOUBLE-BLIND, PLACEBO-CONTROLLED STUDY TO ASSESS ADVERSE EVENTS OF SPECIAL INTEREST (AESI) IN ADULTS WITH ACTIVE, AUTOANTIBODY-POSITIVE SYSTEMIC LUPUS ERYTHEMATOSUS (SLE) RECEIVING BELIMUMAB. (June 2019) - Sheikh, Saira; Scheinberg, Morton; Cheng-Chung Wei, James; Tegzova, Dana; Stohl, William; Mucenic, Tamara; Levy, Roger; Bass, Damon; Ross Terrés, Jorge; Punwaney, Rajesh; Harris, Julia; Thorneloe, Kevin; et al.
Abstract : Background: Belimumab (BEL) is approved in adults with active, autoantibody-positive SLE. Phase 2, 3 and long-term extension studies showed a favourable benefit-risk profile. However, numerical differences in the incidence of mortality, infections, hypersensitivity reactions and some psychiatric events warranted a large, focused safety study to assess these events, along with potential for malignancy. Objectives: To evaluate all-cause mortality and AESI in patients with SLE receiving intravenous (IV) BEL vs placebo (PBO) over 52 weeks. Methods: This study (BASE; BEL115467; NCT01705977 ) randomised adults with SLE (1:1) to monthly BEL 10 mg/kg IV or PBO, plus standard of care, for 48 weeks. No minimum SELENA-SLEDAI disease activity was required and no exclusions for previous psychiatric conditions were made. Differences in rates (95% CI) of mortality and other pre-specified AESI (malignancies, serious infections, opportunistic infections and other infections of interest, serious depression, suicidality [C-SSRS], and serious infusion/hypersensitivity reactions) on-treatment (first to last dose +28 days) were assessed. For on-treatment serious suicidal ideation/behaviour and self-injury events (per sponsor adjudication), and on-study (first dose to end of Week 52 study follow-up) suicidal ideation/behaviour (C-SSRS), differences (95% CI) vs PBO were calculated post hoc. Results: 4003 patients received ≤1 dose. Baseline demographics and disease characteristics were similar between groups. On-treatment mortality and pre-specified AESI rates are shown in the Table 1 below. Overall rates of on-treatment AESIs were similar between groups, except for serious depression and serious infusion/hypersensitivity reactions. On-treatment deaths were most frequently caused by infection (3 [0.15%] PBO vs 9 [0.45%] BEL); on-study deaths occurred in 22 (1.10%) PBO and 13 (0.65%) BEL patients (difference [95% CI]: -0.45 [-1.03, 0.13]). On-treatment serious suicidal ideation/behaviour and self-injury events were reported for 5 (0.25%) PBO and 15 (0.75%) BEL patients (difference [95% CI]: 0.50 [0.06, 0.94]); on-study suicidal ideation/behaviour (C-SSRS) occurred in 39 (1.96%) PBO and 48 (2.43%) BEL patients (difference [95% CI]: 0.47 [-0.44, 1.38]). No suicide-related deaths were reported. Conclusion: In this double-blind, placebo-controlled (1:1) safety study, which is the largest SLE clinical study to date with 4003 patients, on-treatment all-cause mortality, infection and malignancy AESI rates were similar between BEL and PBO, with imbalances observed in serious depression, serious suicidal ideation/behaviour and self-injury events, and serious infusion/hypersensitivity reactions. Acknowledgement: We acknowledge the BASE Study Group. Study funding: GSK. Disclosure of Interests: Saira Sheikh Consultant for: GSK, Morton Scheinberg: None declared, James Cheng-Chung Wei Grant/research support from: TSH Biopharm, Abbvie, BMS, Celgene, Janssen, Novartis, Pfizer and UCB, Consultant for: TSH biopharm, Abbvie, BMS, Celgene, Chugai, Eisai, Janssen, Novartis, Pfizer, Sanofi-Aventis and UCB pharma, Dana Tegzova: None declared, William Stohl Grant/research support from: GSK, Consultant for: Janssen R&D, Tamara Mucenic Grant/research support from: GSK, Janssen, Roche, Eli Lilly, Pfizer, Amgen, Consultant for: Janssen, Roche, UCB, Novartis, Speakers bureau: Janssen, Roche, UCB, Novartis, Abbvie, Pfizer, Roger Levy Shareholder of: GSK, Employee of: GSK, Damon Bass Shareholder of: GSK, Employee of: GSK, Jorge Ross Terrés Shareholder of: GSK, Employee of: GSK at the time of study, Rajesh Punwaney Shareholder of: GSK, Employee of: GSK, Julia Harris Shareholder of: GSK, Employee of: GSK, Kevin Thorneloe Shareholder of: GSK, Employee of: GSK, Beulah Ji Shareholder of: GSK, Employee of: GSK, David Roth Shareholder of: GSK, Employee of: GSK